Graduate Students' Opınıons on the Scıentıfıc Research - Et, Sümeyra Zeynep; Gömleksiz, Mehmet Nuri (Gaziantep Üniversitesi, 2022)
The existence of individuals who have the competence to conduct scientific research is very important for countries to have a say in fields such as science and technology. For this reason, training of individuals who have the competence to conduct scientific research is among the goals of education systems. Higher education and graduate education levels are among the institutions that take the training of individuals with this qualification as a mission. In this context, it is thought that different studies on the scientific research competencies of individuals who continue their postgraduate education are important. The aim of this study is to determine the opinions of individuals who continue their graduate education on the scientific research process. The data collection tool of the research conducted in accordance with the qualitative research design is a semi-structured interview form. The study group of the research consists of 30 graduate and doctoral students. Some of the results obtained are as follows: It has been determined that they pay attention to the elements of "the aim of the research and the problem situation" while determining the method of the research. In addition, it is possible to say that the participants felt incomplete in the analysis of the research data and the development of measurement tools suitable for their research.

Bilimsel araştırma yapma yeterliğine sahip bireylerin varlığı ülkelerin bilim ve teknoloji gibi alanlarda söz sahibi olmaları bakımından oldukça önemlidir. Bu nedenle eğitim sistemlerinin hedefleri arasında bilimsel araştırma yapma yeterliğine sahip bireylerin yetiştirilmesi yer almaktadır. Yüksek öğretim ve lisansüstü eğitim kademeleri ise bu yeterliliğe sahip bireylerin yetiştirilmesini misyon edinen kurumlardandır. Bu bağlamda lisansüstü eğitime devam eden bireylerin bilimsel araştırma yeterlikleri ile ilgili yapılacak farklı çalışmaların önemli olduğu düşünülmektedir. Lisansüstü eğitime devam eden bireylerin bilimsel araştırma sürecine ilişkin görüşlerinin belirlenmesi bu araştırmanın amacını oluşturmaktadır. Nitel araştırma desenine uygun olarak yürütülen araştırmanın veri toplama aracını ise yarı yapılandırılmış görüşme formu oluşturmaktadır. Araştırmanın çalışma grubunu 30 yüksek lisans ve doktora öğrencisi oluşturmaktadır. Elde edilen sonuçlardan bazıları ise şu şekildedir: lisansüstü araştırmanın problem durumunu belirlerken en fazla orijinal olması ve bilime katkı sağlaması”, araştırmanın yöntemini belirlerken “araştırmanın amacı ve problem durumu” unsurlarına dikkat ettikleri tespit edilmiştir. Bunun yanı sıra araştırma verilerinin analizi ve araştırmalarına uygun ölçme aracı geliştirme noktalarında katılımcıların kendilerini eksik hissettiklerini söylemek mümkündür.
Lisansüstü Öğrencilerin Bilimsel Araştırma Sürecine İlişkin Görüşleri
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar